Difference between revisions of "2024 AMC 12A Problems/Problem 23"
Ericzzzqwq (talk | contribs) (→Solution 6 (Half angle formula twice)) |
The 76923th (talk | contribs) m (→Alternate proof of the two tangent squares formula) |
||
(25 intermediate revisions by 10 users not shown) | |||
Line 51: | Line 51: | ||
~tsun26 | ~tsun26 | ||
− | ==Solution 2 (Another | + | ==Solution 2 (Another Identity)== |
First, notice that | First, notice that | ||
Line 130: | Line 130: | ||
~[https://artofproblemsolving.com/wiki/index.php/User:KEVIN_LIU KEVIN_LIU] | ~[https://artofproblemsolving.com/wiki/index.php/User:KEVIN_LIU KEVIN_LIU] | ||
− | ==Solution | + | ==Solution 5 (Transformation)== |
− | |||
− | + | Set x = <math>\pi/16</math> , 7x = <math>\pi/2</math> - x , | |
− | |||
− | |||
set C7 = <math>cos^2(7x)</math> , C5 = <math>cos^2(5x)</math>, C3 = <math>cos^2(3x)</math>, C= <math>cos^2(x)</math> , S2 = <math>sin^2(2x)</math> , S6 = <math>sin^2(6x), etc.</math> | set C7 = <math>cos^2(7x)</math> , C5 = <math>cos^2(5x)</math>, C3 = <math>cos^2(3x)</math>, C= <math>cos^2(x)</math> , S2 = <math>sin^2(2x)</math> , S6 = <math>sin^2(6x), etc.</math> | ||
Line 153: | Line 150: | ||
~[https://artofproblemsolving.com/wiki/index.php/User:Cyantist luckuso] | ~[https://artofproblemsolving.com/wiki/index.php/User:Cyantist luckuso] | ||
+ | |||
==Solution 6 (Half angle formula twice)== | ==Solution 6 (Half angle formula twice)== | ||
So from the question we have: | So from the question we have: | ||
Line 169: | Line 167: | ||
<cmath>=(\frac{1+\cos\frac{\pi}{8}}{1-\cos\frac{\pi}{8}}+\frac{1-\cos\frac{\pi}{8}}{1+\cos\frac{\pi}{8}})(\frac{1+\cos\frac{3\pi}{8}}{1-\cos\frac{3\pi}{8}}+\frac{1-\cos\frac{3\pi}{8}}{1+\cos\frac{3\pi}{8}})</cmath> | <cmath>=(\frac{1+\cos\frac{\pi}{8}}{1-\cos\frac{\pi}{8}}+\frac{1-\cos\frac{\pi}{8}}{1+\cos\frac{\pi}{8}})(\frac{1+\cos\frac{3\pi}{8}}{1-\cos\frac{3\pi}{8}}+\frac{1-\cos\frac{3\pi}{8}}{1+\cos\frac{3\pi}{8}})</cmath> | ||
− | <cmath>()()</cmath> | + | <cmath>=(\frac{(1+\cos\frac{\pi}{8})^2+(1-\cos\frac{\pi}{8})^2}{1-\cos^2\frac{\pi}{8}})(\frac{(1+\cos\frac{3\pi}{8})^2+(1-\cos\frac{3\pi}{8})^2}{1-\cos^2\frac{3\pi}{8}})</cmath> |
+ | |||
+ | <cmath>=(\frac{2+2\cos^2\frac{\pi}{8}}{1-\cos^2\frac{\pi}{8}})(\frac{2+2\cos^2\frac{3\pi}{8}}{1-\cos^2\frac{3\pi}{8}})</cmath> | ||
+ | |||
+ | Using <math>\cos^2\frac{\theta}{2}=\frac{1+\cos\theta}{2}</math> | ||
+ | |||
+ | <cmath>=(\frac{2+1+\cos\frac{\pi}{4}}{1-\frac{1+\cos\frac{\pi}{4}}{2}})(\frac{2+1+\cos\frac{3\pi}{4}}{1-\frac{1+\cos\frac{3\pi}{4}}{2}})</cmath> | ||
+ | |||
+ | <cmath>=(\frac{12+2\sqrt{2}}{4-2\sqrt{2}})(\frac{12-2\sqrt{2}}{4+2\sqrt{2}})</cmath> | ||
+ | |||
+ | <cmath>=\frac{136}{2}=\boxed{\textbf{B) }68 }</cmath> | ||
+ | |||
+ | ~ERiccc | ||
+ | ==Solution 7(single formula)== | ||
+ | <cmath>\cot \alpha - \tan \alpha = 2 \cot 2 \alpha \implies \cot^2 \alpha + \tan^2 \alpha = 4 \cot^2 2 \alpha + 2.</cmath> | ||
+ | We use <math>\alpha = \frac {\pi}{16}</math> for <math>(\tan^2\frac{\pi}{16}+\tan^2 \frac{7\pi}{16})(\tan^2\frac{3\pi}{16}+\tan^2 \frac{5\pi}{16}).</math> | ||
+ | |||
+ | <cmath>(\tan^2 \alpha + \cot^2 \alpha)(\tan^2 (\frac{\pi}{4} - \alpha) + \cot^2 (\frac{\pi}{4} - \alpha)) = (4 \cot^2 2 \alpha + 2)(4 \cot^2 (\frac{\pi}{2} - 2\alpha) +2) =</cmath> | ||
+ | <cmath>= 4 \cdot(4+ 2\tan^2 2\alpha + 2\cot^2 2\alpha +1) = 20 + 8 \cdot (4 \cot^2 4 \alpha +2) = 68.\blacksquare</cmath> | ||
+ | '''vladimir.shelomovskii@gmail.com, vvsss''' | ||
+ | |||
+ | ==Solution 8(just do it ✅)== | ||
+ | Since A is too big and E is too small, There is only 3 options left, you can make a guess now, however, estimating the value of it is also okay. You will get 68 for the final answer. | ||
+ | |||
+ | ==Solution 9 (Vietas)== | ||
+ | As the above solutions noted, we can factor the expression into <math>(\tan^2\frac{\pi}{16}+\tan^2 \frac{7\pi}{16})(\tan^2\frac{3\pi}{16}+\tan^2 \frac{5\pi}{16})</math>. | ||
+ | |||
+ | Before we directly solve this problem, let's analyze the roots of <math>\tan(4\tan^{-1}{x}) = 1</math>, or equivalently using tangent expansion formula, <math>\frac{1-6x^2+x^4}{4x-4x^3}=1</math>, which implies <math>x^4+4x^3-6x^2-4x+1=0</math>. Now note that the roots of this equation are precisely <math>\tan\frac{\pi}{16}, \tan\frac{5\pi}{16}, \tan\frac{9\pi}{16}, \tan\frac{13\pi}{16}</math>, so the second symmetric sum of these four numbers is <math>6</math> by Vieta's. Thus, we have <cmath>\tan\frac{\pi}{16}\tan\frac{5\pi}{16}+\tan\frac{\pi}{16}\tan\frac{9\pi}{16}+\tan\frac{\pi}{16}\tan\frac{13\pi}{16}+\tan\frac{5\pi}{16}\tan\frac{9\pi}{16}+\tan\frac{5\pi}{16}\tan\frac{13\pi}{16}+\tan\frac{9\pi}{16}\tan\frac{13\pi}{16}=6</cmath> | ||
+ | Upon further inspection, <math>\tan\frac{\pi}{16}\tan\frac{9\pi}{16}+\tan\frac{5\pi}{16}\tan\frac{13\pi}{16}=-2</math> using the fact that <math>\tan(x)*\tan(x + \pi/2) = -1</math>. Hence, we have <cmath>\tan\frac{\pi}{16}\tan\frac{5\pi}{16}-1+\tan\frac{\pi}{16}\tan\frac{13\pi}{16}+\tan\frac{5\pi}{16}\tan\frac{9\pi}{16}-1+\tan\frac{9\pi}{16}\tan\frac{13\pi}{16}=6</cmath> | ||
+ | <cmath>\tan\frac{\pi}{16}\tan\frac{5\pi}{16}+\tan\frac{\pi}{16}\tan\frac{13\pi}{16}+\tan\frac{5\pi}{16}\tan\frac{9\pi}{16}+\tan\frac{9\pi}{16}\tan\frac{13\pi}{16}=8</cmath> | ||
+ | <cmath>(\tan\frac{\pi}{16}+\tan\frac{9\pi}{16})(\tan\frac{5\pi}{16}+\tan\frac{13\pi}{16})=8</cmath> | ||
+ | |||
+ | Now, we return to the problem statement, where we see a similar squared sum. We use this motivation to square our equation above to obtain | ||
+ | |||
+ | <cmath>(\tan^2\frac{\pi}{16}+\tan^2\frac{9\pi}{16}-2)(\tan^2\frac{5\pi}{16}+\tan^2\frac{13\pi}{16}-2)=64</cmath> | ||
+ | <cmath>(\tan^2\frac{\pi}{16}+\tan^2\frac{9\pi}{16})(\tan^2\frac{5\pi}{16}+\tan^2\frac{13\pi}{16})-2(\tan^2\frac{\pi}{16}+\tan^2\frac{5\pi}{16}+\tan^2\frac{9\pi}{16}+\tan^2\frac{13\pi}{16})+4=64</cmath> | ||
+ | <cmath>(\tan^2\frac{\pi}{16}+\tan^2\frac{9\pi}{16})(\tan^2\frac{5\pi}{16}+\tan^2\frac{13\pi}{16})-2(\tan^2\frac{\pi}{16}+\tan^2\frac{5\pi}{16}+\tan^2\frac{9\pi}{16}+\tan^2\frac{13\pi}{16})=60</cmath> | ||
+ | Then, use the fact that <math>\tan^2{x}=\tan^2{\pi/2-x}</math> to get | ||
+ | <cmath>(\tan^2\frac{\pi}{16}+\tan^2\frac{7\pi}{16})(\tan^2\frac{3\pi}{16}+\tan^2\frac{5\pi}{16})-2(\tan^2\frac{\pi}{16}+\tan^2\frac{5\pi}{16}+\tan^2\frac{9\pi}{16}+\tan^2\frac{13\pi}{16})=60</cmath> | ||
+ | Hold on; the first term is exactly what we are solving for! It thus suffices to find <math>\tan^2\frac{\pi}{16}+\tan^2\frac{5\pi}{16}+\tan^2\frac{9\pi}{16}+\tan^2\frac{13\pi}{16}</math>. Fortunately, this is just <math>{S_1}^2-2{S_2}</math> (Where <math>S_n</math> is the nth symmetric sum), with relation to roots of <math>x^4+4x^3-6x^2-4x+1=0</math>. By Vieta's, this is just <math>(-4)^2-2(6)=4</math>. | ||
+ | |||
+ | Finally, we plug this value into our equation to obtain | ||
+ | <cmath>(\tan^2\frac{\pi}{16}+\tan^2\frac{7\pi}{16})(\tan^2\frac{3\pi}{16}+\tan^2\frac{5\pi}{16})-2(4)=60</cmath> | ||
+ | <cmath>(\tan^2\frac{\pi}{16}+\tan^2\frac{7\pi}{16})(\tan^2\frac{3\pi}{16}+\tan^2\frac{5\pi}{16})=\boxed{68}</cmath> | ||
+ | |||
+ | ==Alternate proof of the two tangent squares formula== | ||
+ | |||
+ | We want to simplify <math>\tan^{2}(x)</math> + <math>\tan^{2}(\frac{\pi}{2} - x)</math>. We make use of the fact that <math>\tan(\frac{\pi}{2} - x)</math> = <math>\cot(x)</math>.Then, the expression becomes <math>\tan^{2}(x)</math> + <math>\cot^{2}(x)</math>. | ||
+ | Notice we can write: | ||
+ | <math>(\tan x + \cot x)^{2}</math> as <math>\tan^{2}(x)</math> + <math>\cot^{2}(x)</math> + 2 as tangent and cotangent are reciprocals of each other. Then, the sum of the tangent and cotangent can be simplified to <math>\frac{\sec^{2}{x}}{\tan x}</math>. Using the fact that secant is the reciprocal of cosine and tangent is the ratio of sine and cosine, we can simplify that expression to <math>\frac{1}{\sin x \cos x}</math>. So, we have that: <math>\tan^{2}(x)</math> + <math>\cot^{2}(x)</math> = <math>\frac{1}{(\sin x \cos x)^2} - {2}</math> which can be simplfied to: <math>2\Bigr(\frac{2}{\sin^{2}(2x)} - 1\Bigr)</math> or <math>\frac{4}{\sin^{2}(2x)} - 2</math> as stated in earlier solutions. | ||
+ | |||
+ | ~ilikemath247365 | ||
==See also== | ==See also== | ||
{{AMC12 box|year=2024|ab=A|num-b=22|num-a=24}} | {{AMC12 box|year=2024|ab=A|num-b=22|num-a=24}} | ||
{{MAA Notice}} | {{MAA Notice}} |
Latest revision as of 20:05, 27 December 2024
Contents
- 1 Problem
- 2 Solution 1 (Trigonometric Identities)
- 3 Solution 2 (Another Identity)
- 4 Solution 3 (Complex Numbers)
- 5 Solution 5 (Transformation)
- 6 Solution 6 (Half angle formula twice)
- 7 Solution 7(single formula)
- 8 Solution 8(just do it ✅)
- 9 Solution 9 (Vietas)
- 10 Alternate proof of the two tangent squares formula
- 11 See also
Problem
What is the value of
Solution 1 (Trigonometric Identities)
First, notice that
Here, we make use of the fact that
Hence,
Note that
Hence,
Therefore, the answer is .
~tsun26
Solution 2 (Another Identity)
First, notice that
Here, we make use of the fact that
Hence,
Therefore, the answer is .
Solution 3 (Complex Numbers)
Let . Then,
Expanding by using a binomial expansion,
Divide by
and notice we can set
where
. Then, define
so that
Notice that we can have because we are only considering the real parts. We only have this when
, meaning
. This means that we have
as unique roots (we get them from
) and by using the fact that
, we get
Since we have a monic polynomial, by the Fundamental Theorem of Algebra,
Looking at the
term in the expansion for
and using vietas gives us
Since
and
Therefore
Solution 5 (Transformation)
Set x = , 7x =
- x ,
set C7 =
, C5 =
, C3 =
, C=
, S2 =
, S6 =
First, notice that
Solution 6 (Half angle formula twice)
So from the question we have:
Using
Using
Using
~ERiccc
Solution 7(single formula)
We use
for
vladimir.shelomovskii@gmail.com, vvsss
Solution 8(just do it ✅)
Since A is too big and E is too small, There is only 3 options left, you can make a guess now, however, estimating the value of it is also okay. You will get 68 for the final answer.
Solution 9 (Vietas)
As the above solutions noted, we can factor the expression into .
Before we directly solve this problem, let's analyze the roots of , or equivalently using tangent expansion formula,
, which implies
. Now note that the roots of this equation are precisely
, so the second symmetric sum of these four numbers is
by Vieta's. Thus, we have
Upon further inspection,
using the fact that
. Hence, we have
Now, we return to the problem statement, where we see a similar squared sum. We use this motivation to square our equation above to obtain
Then, use the fact that
to get
Hold on; the first term is exactly what we are solving for! It thus suffices to find
. Fortunately, this is just
(Where
is the nth symmetric sum), with relation to roots of
. By Vieta's, this is just
.
Finally, we plug this value into our equation to obtain
Alternate proof of the two tangent squares formula
We want to simplify +
. We make use of the fact that
=
.Then, the expression becomes
+
.
Notice we can write:
as
+
+ 2 as tangent and cotangent are reciprocals of each other. Then, the sum of the tangent and cotangent can be simplified to
. Using the fact that secant is the reciprocal of cosine and tangent is the ratio of sine and cosine, we can simplify that expression to
. So, we have that:
+
=
which can be simplfied to:
or
as stated in earlier solutions.
~ilikemath247365
See also
2024 AMC 12A (Problems • Answer Key • Resources) | |
Preceded by Problem 22 |
Followed by Problem 24 |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 • 16 • 17 • 18 • 19 • 20 • 21 • 22 • 23 • 24 • 25 | |
All AMC 12 Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.